2019
DOI: 10.3390/jcm8111903
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EEF1A1 Is Associated with Prognosis of Patients with Colon Adenocarcinoma

Abstract: Background: The prognostic role of the translational factor, elongation factor-1 alpha 1 (EEF1A1), in colon cancer is unclear. Objectives: The present study aimed to investigate the expression of EEF1A in tissues obtained from patients with stage II and III colon cancer and analyze its association with patient prognosis. Methods: A total of 281 patients with colon cancer who underwent curative resection were analyzed according to EEF1A1 expression. Results: The five-year overall survival in the high-EEF1A1 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…PLA2G4A [86], FGG (fibrinogen gamma chain) [87] and TYMS (thymidylatesynthetase) [88] have been demonstrated to be up regulated in cancer, but these genes might be liable for progression of PDAC. RAB32 [89], SEPTIN4 [90], TPM2 [91], ACOT7 [92], PRTFDC1 [93], CABLES1 [94], HLA-DMB [95], PTPRC (protein tyrosine phosphatase receptor type C) [96], CD5 [97], CD6 [97], MS4A1 [98], CD22 [99], CD27 [100], MRC2 [101], CLEC2D [102], EEF1A1 [103] and APOB (apolipoprotein B) [104] played a predominant role in the cancer progression, but these genes might be associated with development of PDAC. Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2G4A [86], FGG (fibrinogen gamma chain) [87] and TYMS (thymidylatesynthetase) [88] have been demonstrated to be up regulated in cancer, but these genes might be liable for progression of PDAC. RAB32 [89], SEPTIN4 [90], TPM2 [91], ACOT7 [92], PRTFDC1 [93], CABLES1 [94], HLA-DMB [95], PTPRC (protein tyrosine phosphatase receptor type C) [96], CD5 [97], CD6 [97], MS4A1 [98], CD22 [99], CD27 [100], MRC2 [101], CLEC2D [102], EEF1A1 [103] and APOB (apolipoprotein B) [104] played a predominant role in the cancer progression, but these genes might be associated with development of PDAC. Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Then, GO [96], CD5 [97], CD6 [97], MS4A1 [98], CD22 [99], CD27 [100], MRC2 [101], CLEC2D [102], EEF1A1 [103] and APOB (apolipoprotein B) [104] played a predominant role in the cancer progression, but these genes might be associated with development of PDAC. Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has high expression in tumors. Hence, its high level may be considered as a tumor marker [ 78 80 ].…”
Section: Similarities Of Treatment For Cancer and Covid-19mentioning
confidence: 99%
“…High expression of EEF1A1 was reported to predict a favorable overall survival of colon adenocarcinoma patients. 15 According to the data by Lin et al, EEF1A1 mRNA levels are reduced in clinical breast ductal carcinoma specimens. Underexpression of EEF1A1 mRNA predicts poor prognosis for estrogen receptor-positive cancer patients.…”
Section: Introductionmentioning
confidence: 99%